2020
DOI: 10.3390/medicina56090436
|View full text |Cite
|
Sign up to set email alerts
|

Association between Accreditation and In-Hospital Mortality in Patients with Major Cardiovascular Diseases in South Korean Hospitals: Pre-Post Accreditation Comparison

Abstract: The direct impact of hospital accreditation on patients’ clinical outcomes is unclear. The purpose of this study was to evaluate whether mortality within 30 days of hospitalization for acute myocardial infarction (AMI), ischemic stroke (IS), and hemorrhagic stroke (HS) differed before and after hospital accreditation. This study targeted patients who had been hospitalized for the three diseases at the general hospitals newly accredited by the government in 2014. Thirty-day mortality rates of three years before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The most recent systematic study discovered a link between accreditation and efficiency, effectiveness, timeliness, and safety [ 32 ]. Meanwhile, other research has shown a connection between accreditation and clinical outcome improvements such as decreased standardized mortality ratios for chronic illnesses [ 66 , 67 ] and other measures of service quality [ 68 ]. However, other studies have shown no correlation between accreditation and clinical outcomes [ 59 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent systematic study discovered a link between accreditation and efficiency, effectiveness, timeliness, and safety [ 32 ]. Meanwhile, other research has shown a connection between accreditation and clinical outcome improvements such as decreased standardized mortality ratios for chronic illnesses [ 66 , 67 ] and other measures of service quality [ 68 ]. However, other studies have shown no correlation between accreditation and clinical outcomes [ 59 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies consistently show a link between being accredited and better patient outcomes. For example, one research paper discovered that hospitals with recognized accreditation had surgery complications and improved patient recovery rates compared to those without accreditation (16,17). The importance of accreditation in improving patient care is highlighted by the impact it has on individuals receiving healthcare services.…”
Section: Manifestationmentioning
confidence: 99%
“…There is a need for new evaluation tools and new reference frames, which, with the support of indicators and digital applications, can achieve this desired change [ 11 ]. The new governance models applied in hospitals that meet the requirements of the patient-centered care process and have a high potential for improvement in providing medical care are demonstrated including by lower mortality rates in orthopedic departments [ 12 ].…”
Section: Introductionmentioning
confidence: 99%